Korelasi Jumlah CD4 Pasien Yang Diberi Isoniazid Dengan Ko-infeksi TB Pada Pasien HIV/AIDS - Niken Ayu Farida Salim; Zulfian; Neno Fitriyani Hasbie; Arif Effendi (ARTERI : Jurnal Ilmu Kesehatan, 2020)
The interaction between TB and HIV infection is complex. In HIV-infected individuals, this situation will decrease the immune system and increase vulnerability to TB incidence. HIV causes reactivation, reinfection, and progression of latent TB infection to active tuberculosis. It also led to differences in the clinical presentation of TB in HIV patients, complications, and response to anti-TB treatment than in HIV negative patients. The purpose of this study To Know Correlation CD4 counts in patients with HIV / AIDS in hospitals Dr.H. Abdul Moeloek Lampung Province 2018. Research methods: cross-sectional approach, in which several variables tested in this research object data got from the medical record. Analysis of the data used is the Mann-Whitney statistical test. Research The total sample of 160 medical records of patients seen that the Asymp. Sig. (2-tailed) is 0,000. Half of this significance value ½ (0.000) is <0.05. It can be concluded that reject H0 and Ha accepted, which implies a significant difference in CD4 cell counts in patients given isoniazid as TB prevention with patients TB co-infection. With all forces, correlation means that their relationship CD4 cell counts in patients given isoniazid to prevent TB and TB co-infection. There is a significant relationship between CD4 cell count in patients who given isoniazid for the prevention of TB and TB co-infection in HIV / AIDS patients in hospitals Dr.H. Abdul Moeloek Lampung Province 2018.